Before and after GDPR: Tracking in mobile apps - Konrad Kollnig; Reuben Binns; Max Van Kleek; Jun Zhao; Ulrik Lyngs; Claudine Tinsman; Nigel Shadbolt (Internet Policy Review, 2021)
Third-party tracking, the collection and sharing of behavioural data about individuals, is a significant and ubiquitous privacy threat in mobile apps. The EU General Data Protection Regulation (GDPR) was introduced in 2018 to protect personal data better, but there exists, thus far, limited empirical evidence about its efficacy. This paper studies tracking in nearly two million Android apps from before and after the introduction of the GDPR. Our analysis suggests that there has been limited change in the presence of third-party tracking in apps, and that the concentration of tracking capabilities among a few large gatekeeper companies persists. However, change might be imminent.
Keywords: 300; Personal data; Personal data protection; Mobile apps; Privacy; GDPR; Competition